2014
DOI: 10.3390/f5050936
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Influence of Plot Size and LiDAR Density on Forest Structure Attribute Estimates

Abstract: This paper assesses the combined effect of field plot size and LiDAR density on the estimation of four forest structure attributes: volume, total biomass, basal area and canopy cover. A total of 21 different plot sizes were considered, obtained by decreasing the field measured plot radius value from 25 to 5 m with regular intervals of 1 m. LiDAR data densities were simulated by randomly removing LiDAR pulses until reaching nine different density values. In order to avoid influence of the digital terrain model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
110
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(120 citation statements)
references
References 39 publications
9
110
0
1
Order By: Relevance
“…The high crown diameter of adult P. pinaster trees and AB the regular and homogenous structure of these single-stratified stands could help to obtain good estimates of these parameters related with stand density. Also, the size of the plots of about 1 ha could improve estimates regarding to some other previous mentioned studies, since a minimum plot areas of 500-600 m 2 are needed (Ruiz et al, 2014a). Again, results should be treated with caution because of the scarce number of plots.…”
Section: Discussionmentioning
confidence: 94%
“…The high crown diameter of adult P. pinaster trees and AB the regular and homogenous structure of these single-stratified stands could help to obtain good estimates of these parameters related with stand density. Also, the size of the plots of about 1 ha could improve estimates regarding to some other previous mentioned studies, since a minimum plot areas of 500-600 m 2 are needed (Ruiz et al, 2014a). Again, results should be treated with caution because of the scarce number of plots.…”
Section: Discussionmentioning
confidence: 94%
“…Plot size may also affect the accuracy of estimates of forest structure attributes. In particular, larger plots can increase the accuracy since the edge effect and co-registration errors are significantly reduced as compared with smaller plots (Frazer et al 2011, Ruiz et al 2014. Research has also suggested that accuracy of tree detection in terms of the relative root mean square error (RMSE%) is in the range of 32-89% and the detection rate is in the range of 40-93%.…”
Section: Introductionmentioning
confidence: 99%
“…Laser pulse density and vegetation structure are the most important factors in relation to the height accuracy of the laser-derived Digital Elevation Model (DEM) (Raber et al, 2002;Clark et al, 2004;Valbuena, 2011), especially on steep terrain (Estornell et al, 2011). Furthermore, plot size is an important design parameter in forest surveys, because it has the potential to reduce or inflate the impact of the edge effects and co-registration error, thus affecting the estimated values of forest stand parameters (Ruiz et al, 2014). The accuracy of the results (among other factors) also depends on field measurements and allometric equations used to model variables.…”
Section: Discussionmentioning
confidence: 99%